Hydrodynamic modeling of thermochemical treatment of low permeable kerogen-containing reservoirs - Kravchenko M.N.; Dieva N.N.; Lishchuk A.N.; Muradov A.V.; Vershinin V.E. (Общество с ограниченной ответственностью «Георесурсы», 2018)
The work is devoted to the effectiveness analysis of thermochemical method of intensifying the hydrocarbons inflow using binary mixtures based on ammonium nitrate in the development of lowpermeability reservoirs of unconventional hydrocarbons represented by petroleum-derived kerogen-bearing rocks. The concept of the research is aimed at determining the principles of treating kerogen-bearing layers and the creation of new scientific, methodological and technological solutions to increase the efficiency of developing deposits of these unconventional hydrocarbon reserves. Some properties of oil source formations located on the territory of the Russian Federation are generalized and structured. The results of investigations of the thermal treatment on rocks of the Bazhenov formation are generalized. The authors present the principles of mathematical modeling of thermal and chemical processes, allowing to take into account the geological and hydrodynamic features of kerogen-containing rocks. We have described a mathematical model of the thermogas chemical treatment with the use of binary mixtures. The calculation results of the treating the field with highly viscous oil are given. Based on the calculation results of thermal-gas-chemical treatment (TGCT) of low-permeable reservoir with highly viscous oil, a positive effect was obtained. Therefore, the authors conclude that the TGCT method, along with the search for other methods for the development of kerogen-containing reservoirs, can be considered promising and possibly more optimal than the thermal and chemical methods used.
Keywords: unconventional sources of hydrocarbons; kerogen; kerogen-containing rocks; thermochemical methods; mathematical modeling; generation of hydrocarbons